The effect of beryllium oxide on retention in JET ITER-like wall tiles. (May 2019) - Makepeace, C.; Pardanaud, C.; Roubin, P.; Borodkina, I.; Ayres, C.; Coad, P.; Baron-Wiechec, A.; Jepu, I.; Heinola, K.; Widdowson, A.; Lozano-Perez, S.; J.E.T. Contributors,
Highlights: Oxidation of JET beryllium tiles investigated. Beryllium deuteroxide found with Raman spectroscopy and further investigated with EELS. Oxidation and hydroxide formation is one of three mechanisms of retention in JET. Deuteroxides are formed, as a result of operating conditions (flash heating and melt formation). Co-deposition however, remains the largest contributor to retention. Abstract: Preliminary results investigating the microstructure, bonding and effect of beryllium oxide formation on retention in the JET ITER-like wall beryllium tiles, are presented. The tiles have been investigated by several techniques: Scanning Electron Microscopy (SEM) equipped with Energy Dispersive X-ray (EDX), Transmission Electron microscopy (TEM) equipped with EDX and Electron Energy Loss Spectroscopy (EELS), Raman Spectroscopy and Thermal Desorption Spectroscopy (TDS). This paper focuses on results from melted materials of the dump plate tiles in JET. From our results and the literature, it is concluded, beryllium can form micron deep oxide islands contrary to the nanometric oxides predicted under vacuum conditions. The deepest oxides analyzed were up to 2-micron thicknesses. The beryllium Deuteroxide (BeOx Dy ) bond was found with Raman Spectroscopy. Application of EELS confirmed the oxide presence and stoichiometry. Literature suggests these oxides form at temperatures greater than 700 °C where self-diffusion of beryllium ions through the surface oxide layer can occur. Further oxidation is made possible between oxygen plasma impurities and the beryllium ions now present at the wall surface. Under Ultra High Vacuum (UHV) nanometric Beryllium oxide layers are formed and passivate at room temperature. After continual cyclic heating (to the point of melt formation) in the presence of oxygen impurities from the plasma, oxide growth to the levels seen experimentally (approximately two microns) is proposed. This retention mechanism is not considered to contribute dramatically to overall retention in JET, due to low levels of melt formation. However, this mechanism, thought the result of operation environment and melt formation, could be of wider concern to ITER, dependent on wall temperatures.